Gastric Intelligence - How Homeopathy Regulates the Body’s “Second Brain” in Indigestion (Homoeopathy for All, 2025)
The human gastrointestinal system  is far more than a digestive organ;  it is an intricate neuro-biological  network often referred to as the  body’s “second brain.” This  concept arises from the enteric  nervous system (ENS), a vast  collection of over 100 million  neurons capable of independently  regulating motility, secretion, and  sensory perception without direct  cortical input. Disturbances in  this neuro-gastrointestinal axis  are now recognized as central to  the development of indigestion as  acute course or functional dyspepsia  (FD) in chronic course, a condition  characterized by postprandial  fullness, early satiety, epigastric  discomfort, bloating, nausea, and  impaired gastric accommodation.
Keywords: gastric accommodation; visceral hypersensitivity; perficial symptoms; sensitivity